2018
DOI: 10.1371/journal.pntd.0006266
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of cholera toxin with nanoparticle decoys for treatment of cholera

Abstract: Diarrheal diseases are a major cause of morbidity and mortality worldwide. In many cases, antibiotic therapy is either ineffective or not recommended due to concerns about emergence of resistance. The pathogenesis of several of the most prevalent infections, including cholera and enteroxigenic Escherichia coli, is dominated by enterotoxins produced by lumen-dwelling pathogens before clearance by intestinal defenses. Toxins gain access to the host through critical host receptors, making these receptors attracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…The main inconvenient of this approach would be the possible threat which ZnO NPs would suppose for the environment [ 107 ]. Another current work has demonstrated that GM1 ganglioside-coated PLGA hybrid NPs able to recruit cholera toxin and impede its interaction with its receptor in enterocytes by using a murine in vivo model [ 108 ]. The biodegradable character of PLGA NPs made them more clinically applicable and harmless to the environment.…”
Section: Nanoparticles and Human Infectionsmentioning
confidence: 99%
“…The main inconvenient of this approach would be the possible threat which ZnO NPs would suppose for the environment [ 107 ]. Another current work has demonstrated that GM1 ganglioside-coated PLGA hybrid NPs able to recruit cholera toxin and impede its interaction with its receptor in enterocytes by using a murine in vivo model [ 108 ]. The biodegradable character of PLGA NPs made them more clinically applicable and harmless to the environment.…”
Section: Nanoparticles and Human Infectionsmentioning
confidence: 99%
“…As happens with other bacterial infections, the appearance of MDR has promoted an urgent need to develop alternative treatments against V. cholera . In that sense, Das and colleges designed surface modified PLGA NPs with PEG and GM1, a key host receptor for choler toxin, as a recruitment and clearance tool of enterotoxin [ 84 ]. Obtained results demonstrated that these PNPs are able to selectively and stably binding cholera toxin, thus neutralizing its actions.…”
Section: Recent Polymeric Nanoparticles Against Most Common Human Bacmentioning
confidence: 99%
“…For example, synthetic nanoparticles based on copolymers of acrylic acid, N-tert-butylacrylamide, N-isopropylacrylamide, and N,N′-methylenebisacrylamide could effectively capture and neutralize the toxicity of a peptide toxin melittin by electrostatic and hydrophobic interactions (Hoshino et al, 2012; Yoshimatsu et al, 2015). By coating monosialotetrahexosylganglioside (GM1), a key host receptor for cholera toxin, on the surface of PLGA nanoparticles, an effective toxin-neutralizing nanoplatform was obtained, which can selectively neutralize the effects of cholera toxin on epithelial cells (Das et al, 2018). Moreover, the GM1-coated nanoparticle decoys effectively attenuated intestinal secretory responses of live V. cholerae in a murine infection model.…”
Section: Biomimetic Nanoparticles For Treatment Of Bacterial Infectionsmentioning
confidence: 99%